Enhancing mathematical critical thinking skills: Guided discovery learning model with Om Jakaw Taksapa media - Asriyanti, Anisa; Andrijati, Noening (UIN Raden Mas Said Surakarta, 2024)
Critical thinking skills are essential for students as they enable rational decision-making and the selection of optimal alternatives, equipping them to navigate the challenges of globalization effectively. This study aims to analyze and compare the impacts of conventional teaching methods with guided discovery learning models, supplemented by Om Jakaw Taksapa media, on the critical thinking abilities of fifth-grade students at SDN Gugus Larasati, Central Java, Indonesia. A quasi-experimental design featuring a nonequivalent control group framework was employed. The study population comprised fifth-grade students from SDN Gugus Larasati in Semarang City, with a cluster random sampling technique used to select a total sample of 61 students. Data collection methods included interviews, observations, and tests. The data were analyzed through quantitative techniques and inferential statistics. The results demonstrated that the t-value exceeded the critical t-value (t-count = 2.733 > t-table = 2.131) and the significance level was below 0.05 (p = 0.015 < 0.05), indicating a statistically significant effect. The guided discovery learning model, enhanced by Om Jakaw Taksapa media, exerted a more substantial influence on students’ critical thinking skills in the context of speed-related concepts compared to conventional methods. This research contributes to the advancement of educational science and underscores the importance of innovative teaching models and interactive media in fostering critical thinking. Additionally, it provides practical insights for educators to enhance classroom engagement and learning outcomes.